322 ADENOSINE REGULATION OF INSULIN SENSITIVITY IN HUMAN SKELETAL MUSCLE: POTENTIAL INVOLVEMENT OF THE AKT SIGNALING PATHWAY. (10th December 2015) - Freeby, M.; Aroda, V.; Carter, L.; Henry, R. R.; Ciaraldi, T. P.
Abstract : It is known that adenosine (Ad) plays a role in the maintenance of insulin sensitivity for regulation of metabolism in adipose tissue. The documented impaired insulin sensitivity for stimulation of glucose transport in adipocytes from subjects with Polycystic Ovary Syndrome (PCOS) can be normalized by addition of an adenosine analog (N6-phenylisopropyladenosine, PIA). The involvement of adenosine in skeletal muscle metabolism and insulin action is less clear. To investigate this question, skeletal muscle biopsies were obtained from obese healthy individuals and weight matched individuals with PCOS. Myocyte precursors were isolated and cultured to obtain fully differentiated myotubules (MT). MT were acutely exposed to a range (0-33 nM) of insulin concentrations and glucose uptake (GU) measured. Unlike the situation in adipocytes, removal of endogenous Ad did not influence insulin sensitivity in MT from either normal or PCOS subjects. However, PIA addition increased insulin action seen at a submaximal hormone level (0.41 nM); 61 ± 6% of maximal insulin effect + PIA vs. 27 ± 7% in control cells (p≤0.0005). The effect was similar in normal and PCOS MT. Basal and maximally insulin-stimulated GU activities were not influenced by PIA addition. Signaling pathways involved in GU stimulation were investigated by monitoring changes in the phosphorylation of Akt, PKCξ/λ and AMPK. AMPK phosphorylation was not influenced by either insulin or PIA. Insulin stimulated PKCξ/λ phosphorylation, independent of PIA. Insulin stimulation of Akt phosphorylation at submaximal insulin levels was increased with PIA. Maximally stimulated Akt phosphorylation was reduced in control PCOS MT compared to normal cells and doubled, but not normalized, with PIA treatment. Summary and conclusions: 1) Ad is necessary for the maintenance of insulin sensitivity in skeletal muscle, 2) in the resting state this Ad must be provided by cells other that MT, possibly adipocytes, 3) the Akt pathway may be involved in both Ad regulation of insulin sensitivity and the insulin resistance that commonly occurs in PCOS.